Resistência ao glyphosate em populações de azevém: estudo de aspectos moleculares e da dinâmica populacional suportando modelos preditivos para controle - Pagnoncelli Junior, Fortunato de Bortoli (2020)
Ryegrass (Lolium spp.) is a weed widely spread in farming areas around the world. Due to its rusticity and high growth rate, this species is widely cultivated, both for soil cover and forage production. The intensive use of herbicides with the same mechanism has led to the selection of herbicide-resistant Italian ryegrass populations, especially to glyphosate. The objectives of this thesis were: 1) Characterize the response to glyphosate and assess the resistance index in Italian ryegrass populations collected in the South and Southwest Regions of Paraná State. 2) Study the involvement of a target site mechanism resistance to glyphosate in Italian ryegrass populations. 3) Get information on the demography of Italian ryegrass populations, susceptible and resistant to glyphosate. 4) Develop and validate an empirical model to describe Italian ryegrass emergence based on soil thermal accumulation. 5) Develop a cohort-stochastic model of Italian ryegrass population dynamics in susceptible and glyphosate resistant populations and simulate management strategies for this species under the effect of two climate scenarios. Several experiments have been developed in the greenhouse, laboratory and field of UTFPR, Campus Pato Branco, Brazil and IAS/CSIC, Córdoba, Spain. In farming areas in the South and Southwest Regions of Paraná State, seeds samples from 44 Italian ryegrass populations were collected and tested for glyphosate response. In resistant (MR20AR, VT05AR and RN02AR) and susceptible (MR05AS, VT07AS and RN01AS) populations to glyphosate, the target site mechanism herbicide resistance was investigated. For the demography study, in resistant and susceptible populations, the parameters, emergence, survival and potential for seed production were evaluated. The model based on thermal accumulation to describe the Italian ryegrass emergence was developed and validated. The demographic parameters were combined with literature data to develop a population dynamics model for susceptible and resistant populations, including different management strategies and the effect of the average temperature increase of 2.5°C. High variability in response of Italian ryegrass populations to glyphosate was observed, with resistance index ranging from 1.37 to 5.5. In two populations (MR20AR and RN02AR), an increase in the number of copies of the EPSPs gene (11 to 57x) was detected. Regarding demography, under favourable conditions, seedlings have a rapid emergence (≈30 days), survival depends on plant cohorts (average 2 to 10%), seed production is strongly adjusted by plant density (90% with 50 pl m-2) in both populations. Resistant populations (13830 s pl-1) differed from the susceptible (20300 s pl-1) only in the seed production potential in low-density. The model based on the soil thermal accumulation proved efficient in describing the seedlings emergence, requiring 390 TT for the beginning of the emergence and 590 TT to reach 90% emergence. The population dynamics model showed that the seed bank of susceptible and resistant populations tends to stabilize at similar levels (≈20000 s m-2) and that the average temperature increase of 2.5°C resulted in an increase in the number of seeds present in the bank (≈25000 s m-2). Chemical management strategies and crop rotation with soybean/oat or corn/wheat demonstrated high efficiency and were able to suppress the Italian ryegrass seed bank by more than 75%. It is concluded that gene amplification is a mechanism involved in resistance of Italian ryegrass plants to glyphosate in South Region of Brazil. The predictive models developed in this thesis provide a better understanding of Italian ryegrass population development and the thermal model for emergence, could be used as a tool to assist in this species management.